PENGUNGKAPAN ASET KEUANGAN DAN IMPAIRMENT PADA SEKTOR PERBANKAN MENURUT PSAK 60 DI INDONESIA - Sri Luna Murdianingrum; Marita Marita (Eksos LPPM, 2015)
This writing discusses the Statement of Financial Accounting Standard (Pemyataan StandarAkuntansi Keuangan/PSAK) 60. This study is limited into the measure of time from 2010until today, focuses on standard governing the presentation and disclosure of financialinstruments. This standard is very influential on the Indonesian banking disclose detailsof financial assets and the impairment of assets in the financial statements.So, this study aimed to describe the level of compliance of banks in Indonesia to implementSFAS.This writing uses the method of data collecting from any sourcesKeywords .• Banking, Financial asset, Impairment, PSAK 50 and 60